Approaches to teaching the poetry of John Gower - Yeager, Robert F.; Gastle, Brian W. (Approaches to teaching world literature, 2011)
Introduction : Gower in context / R.F. Yeager and Brian W. Gastle -- Texts for teaching / Russell A. Peck -- The instructor's library / Peter Nicholson -- Electronic resources / Brian W. Gastle -- Teaching Gower's reception : a poet for all ages / Derek Pearsall -- Social class in the classroom : Gower's estates poetry / Scott Lightsey -- Teaching the Confessio amantis as a humanist document of the first English Renaissance / Russell A. Peck -- Bodily and spiritual healing through conversation and storytelling : genius as physician and confessor in the Confessio amantis / James M. Palmer -- Teaching Gower and the law / Andrea Boboc -- Teaching Gower aloud / Joyce Coleman -- Hearing Gower's rhetoric / Georgiana Donavin -- Gower before Chaucer : teaching narrative and ethics in "The tale of Tereus" / Leonard Koff -- Gower's triple tongue (1) : teaching across Gower's languages / Siân Echard -- Gower's triple tongue (2) : teaching the Balades / R.F. Yeager -- Learning Gower by editing Gower / Erick Kelemen -- Teaching Gower's liminal literature and critical theory / J. Allan Mitchell -- Gender, sexuality, and family ties in the Confessio amantis / María Bullón-Fernández -- Postcolonial/queer : teaching Gower using recent critical theory / Steven F. Kruger -- Gower and The Canterbury tales : the enticement to fraud / Craig E. Bertolet -- The hag transformed : "The tale of Florent," ethical choice, and female desire in late medieval England / James M. Dean -- Teaching "The tale of Constance" in context / R.F. Yeager -- Gower teaching Ovid and the classics / Winthrop Wetherbee -- Gower in the community college curriculum / Carole Lynn McKinney -- Chaucer by default? : difficult choices and teaching the sophomore British literature survey / Susannah M. Chewning -- Teaching Gower in the medieval survey class : historical and cultural contexts and the court of Richard II / S. Elizabeth Passmore -- Gower in seminar : the Confessio amantis as publishing opportunity for graduate students / Peter G. Beidler